An Assessment of the Drivers of Health Care System: An Empirical Evidence from Nigeria (Global Journal of Management and Business Research, 2018)
This study discusses the trend and features of the health care delivery system in Nigeria and delved into examining factors that affect its performance using data obtained from the CBN and World Bank spanning 1980 to 2014. Four models were estimated using different indices -economic and social -of health care system and the OLS technique used for estimation. Results obtained revealed that the states of institution and infrastructure as well as the levels of income and education were very significant determinants of health care system in the country. Government subsidy was not very significant and health policy or reform had no significant impact. Infrastructure, income and education had the expected relationships with all social indicators of health care as they improve life expectancy and reduce infant mortality rate; but were negatively related to the economic index with no significant impact. More so, institution and subsidy had a mixed relationship with the health care system. It recommends that the government, relevant authorities and practitioners in the health sector support policies that would bring about improved quality health outcomes in the country.